Attachment, intimacy and self-disclosure in same-gender and cross-gender friendships - Taslak, Marina (Array, 2010)
The aim of this study was to test the differences in the levels of attachment, intimacy and self-disclosure towards the best friend with respect to the dyad type, as well as to determine the accordance on the variables among friends in regard to dyad type (same-gender and cross-gender friendship). We also tested whether this accordance was at lower or higher levels of measured variables considering the dyad type. We examined attachment dimensions (anxiety and avoidance), dimensions of intimacy (knowing a friend, self-sufficiency of a friendship, confidence and loyalty) as well as self-disclosure dimensions (amount, depth, honesty, intent and positive/negative selfdisclosure). The study included 244 dyads (pairs of best friends) aged between 18 and 25. The modification of the Experiences in Close Relationship Inventory (Kamenov and Jelic, 2003), Sharabany Intimacy Scale (1994), and The Revised Scale of Self- Disclosure (Wheelees and Grotz, 1976) were applied. Results have shown the highest anxiety in female-female dyads, while the highest avoidance is present in male-male friendships. Female-female friendships are characterized by the highest levels of intimacy, as well as by the amount and depth of self-disclosure. Men among themselves share more negative information then women. The results on variables accord higher in same-gender then in cross-gender friendships. In male dyads the accordance was on lower level of variables while in female dyads this accordance was on higher level, with the exception of avoidance and negative information sharing, where the situation was opposite.